Equity Dynamics in the Perceived Fairness of Infant Care. Issue 1 (2nd August 2016) - DeMaris, Alfred; Mahoney, Annette
Abstract: How is the perceived fairness of infant care affected by spouses' relative contributions to it and to other domains of their relationship? Longitudinal data on 178 couples expecting the birth of their first child were collected during a period spanning approximately the first year of the child's life. Overall, wives were more likely than husbands to see infant care as fair to the wife. Net of fathers' contributions to infant care, spouses were more likely to see infant care as fair to wives the more the father worked in paid labor and did housework and the more wives benefited in the sexual relationship. Fathers' contributions to infant care had a stronger effect on fairness when the child was a son. The findings are consistent with equity predictions in that fathers' compensatory contributions to other domains of marriage counterbalance an unequal workload in the arena of family work.